Musical Poetics - Burmeister, Joachim 1564-1629; Rivera, Benito V. 1936- (New Haven, CT Yale University Press, 1993)
Joachim Burmeister's early seventeenth-century treatise on the making of music is generally acknowledged to be central to the understanding of Baroque musical practice: it was the first systematically to explore the connection between rhetoric and music that became a cornerstone of Baroque musical thought.
Keywords: 17th Century (1601-1700); Music theory; Rhetoric; Germany